URGENSI KERJASAMA ANTAR DAERAH (INTERGOVERNMENTAL) DALAM PENANGANAN BENCANA ALAM DI DAERAH - Ma?ruf, Muhammad Farid; Isbandono, Prasetyo (JPSI (Journal of Public Sector Innovations), 2016)
Indonesia cluster regions have unique geographical and topographical characteristics also have potential for natural disasters. Potential for natural disasters such as volcanic eruptions, earthquake, tsunami, flood and landslide happen almost in every place in Indonesia. In the past, the handling for natural disasters still use rigid and centralized hierarchy bureaucracy approach which has not been able to handle the disasters and handle post disasters appropriately. The decentralization spirit changes handling natural disasters paradigm which giving authority toward regions government to manage the disasters in its territory. However, the big challenge is to synchronize every regions governments perception that natural disasters in regions can be manage only with one institution or region government according to territory border. The natural disasters management which include the pre disasters and post disasters need together management by several government stratum based on intergovernmental networks. The writer used inductive approach method which allow to describing of the result of analysis study of the possibility of cooperative effort between regions through Regional Disaster Department (BPBD) in several areas in East Java that are Malang region, Kediri, Pasuruan and Bojonegoro by knowing the standard and policy/program/activity target, the condition of resource, and the condition social politic and economy. The result of study analysis about handling the disaster have conclusion that the handling effort pre disaster and post disaster are very multi-dimensional. In the context of government authority, handling of disaster not only handle by one region government. This is where the concept of cooperation between regions (intergovernmental networks) in important to be expanded at the local level. The cooperation between local regions have potency the capacity of region government in order to share experiences, share advantages and share task/assessment together in improving the function of public services in each region government. Then, the result of study analysis also concludes the importance to strengthening BPBD institutions to facilitate the cooperation between governments in local regions in order of handling the disasters.